The effect of using e-learning material on hydrocarbon chapter to improve students’ achievement motivation in learning chemistry - Sri Novita Yanda; Yulia Safitri (Fakultas Ilmu Pendidikan UNP)
In the recent years, electronic-based learning has become an option in chemistry learning. Hydrocarbon has one of the subjects that involved microscopic matter, so it could be understood by animation in computer or internet. The purpose of this research is to know the effect of using e-learning material on hydrocarbon chapter to improve students’ achievement motivation. The quantitative method was applied. The study used a survey approach by using questionnaires were developed. Grade XI students’ was a sample research survey-based in two government high school in Tembilahan, Riau Indonesia. The pilot test involved 30 students’ and the results of the test showed that the Cronbach’s Alpha value was 0.796 and 0.773, shows that the instrument has a high reliability. The validity of the instrument also was analyzed based on Pearson correlation. The findings showed that the instrument has valid. The data were collected was analyzed using inferential statistics. The finding showed that there is a significant relationship between using e-learning material and students’ achievement motivation.